Fertility Treatment and Cancers—The Eternal Conundrum: A Systematic Review and Meta-analysis. Issue 6 (June 2021) - Barcroft, Jennifer Frances; Galazis, Nicolas; Jones, Benjamin P.; Getreu, Natalie; Bracewell-Milnes, Timothy; Grewal, Karen J.; Sorbi, Flavia; Yazbek, Joseph; Lathouras, Kostas; Smith, J. Richard; Hardiman, Paul; Thum, Meen-Yau; et al.
Abstract : (Abstracted from Hum Reprod 2021;36:1093–1107) Given the increased risk of ovarian, breast, and endometrial cancers associated with nulliparity, there is a higher inherent cancer risk among patients pursuing fertility treatment (FT) than the general population. Endometrial and breast are hormone-sensitive cancers that carry elevated risk associated with estrogen predominant states including ovarian stimulation.